2012
DOI: 10.11120/plan.2012.00260008
|View full text |Cite
|
Sign up to set email alerts
|

Google Earth and sustainable development education: examples from human and physical geography

Abstract: Google Earth is a web-based virtual globe that has seen increasing use over the past five years as a teaching tool and learning resource for geography, earth and environmental science students. This paper explores some of the potential uses of Google Earth in sustainable development education, and assesses its value for staff and students. Over a two year period, different projects were devised that required undergraduate students to engage with Google Earth and reflect on its value. The projects included a fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
0
1
0
1
Order By: Relevance
“…En este sentido, las herramientas de visualización y modelización topográfica tridimensional de la superficie terrestre que ofrecen diversas plataformas, como Google, son muy eficientes y han sido utilizadas por varios autores. En especial, destaca la herramienta Google Earth o Google My Maps (Gómez Trigueros & Moreno Vera, 2018;Minocha et al, 2018;Schaaf et al, 2012;Thorndycraft et al, 2009). Se trata de un valioso recurso para implementar un viaje/salida virtual con un potencial excelente para la educación geográfica superior (Patterson, 2007).…”
Section: La Virtualización De La Enseñanza Pandemia E Inclusividadunclassified
“…En este sentido, las herramientas de visualización y modelización topográfica tridimensional de la superficie terrestre que ofrecen diversas plataformas, como Google, son muy eficientes y han sido utilizadas por varios autores. En especial, destaca la herramienta Google Earth o Google My Maps (Gómez Trigueros & Moreno Vera, 2018;Minocha et al, 2018;Schaaf et al, 2012;Thorndycraft et al, 2009). Se trata de un valioso recurso para implementar un viaje/salida virtual con un potencial excelente para la educación geográfica superior (Patterson, 2007).…”
Section: La Virtualización De La Enseñanza Pandemia E Inclusividadunclassified
“…As a matter of fact, many studies have been carried out on the impact of GE program on teaching geography subjects (Cruz and Zellers, 2006;Wilson et al, 2009;Chilcott and Haslett, 2010;Cuviello, 2010;Gobert et al, 2012;Schaaf et al, 2013;Thankachan and Franklin, 2013;Öğütveren, 2014;Ayas et al, 2015;Blank et al, 2015;Merç, 2017;Xiang and Liu, 2017;Hsu et al, 2018;Yayla, 2019;Koçak, 2020). These studies conducted about the field have shown that both printed maps and location-based digital GE maps can be used in teaching geography subjects.…”
Section: Introductionmentioning
confidence: 99%